Development and Validation Model of Peatland Conservation through Interdisciplinary Science Learning (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
The peatland conservation model is generally developed based on the community. A new education-based conservation model was developed through temporary activities through seminars, workshops or non-formal learning. The aim of this research is to develop and validation a peatland conservation model through interdisciplinary science learning that connects universities, schools and communities in peatland conservation activities. The development of a peatland conservation model went through third stages following interdisciplinary research patterns. Validation was determined by content and empirical validation. The peatland conservation model consisted of three interrelated dimensions in peatland conservation, namely universities, schools and communities. The model was equipped with implementation tools in the field in the form of science learning tools. The form of a peatland conservation model book, teaching practice materials, an environmental literacy questionnaire, and an interdisciplinary thinking performance rubric were developed in this study. The validated aspects included theory, assumptions, and conceptual model representations with the Aiken score was 0.88 as a valid category and the ICC value of 0.457 showed that the reliability was not good. Empirical validation showed that the dimensions of the university, school and community constructs had internal consistency reliability and validity. The relation between dimension that universities had an influence on schools and society, and schools have an influence on society. The peatland conservation model was equipped with practical teaching learning tools that directly connected universities and schools. However, this model was also suitable for non-educational natural sciences courses or pure natural sciences to form interdisciplinary thinking skills and environmental literacy.